2004
DOI: 10.1128/iai.72.6.3693-3694.2004
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Piscirickettsia salmonis to High Titers in Insect Tissue Culture Cells

Abstract: Piscirickettsia salmonis was grown in established insect, frog, and fish tissue culture cells. The yield of P. salmonis in Sf21 cells was up to 100 times that obtained in CHSE-214 cells, and virulence for Atlantic salmon was retained. The ceiling temperature for growth of P. salmonis in Sf21 cells was 24°C

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 13 publications
0
29
0
1
Order By: Relevance
“…However, Birkbeck et al (2004) showed that P. salmonis replicates in higher titers in an insect cell line than in the CHSE-214 cells that are normally used to culture the organism and that P. salmonis retains virulence for Atlantic salmon Salmo salar after repeated culture in insect cells. On the other hand, the tissue chosen for the isolation of P. salmonis during active infection in salmonids is kidney, and SHK-1 is a cell line from S. salar head kidney, which exhibits macrophage properties (Dannevig et al 1997).…”
Section: Resultsmentioning
confidence: 99%
“…However, Birkbeck et al (2004) showed that P. salmonis replicates in higher titers in an insect cell line than in the CHSE-214 cells that are normally used to culture the organism and that P. salmonis retains virulence for Atlantic salmon Salmo salar after repeated culture in insect cells. On the other hand, the tissue chosen for the isolation of P. salmonis during active infection in salmonids is kidney, and SHK-1 is a cell line from S. salar head kidney, which exhibits macrophage properties (Dannevig et al 1997).…”
Section: Resultsmentioning
confidence: 99%
“…Birkbeck et al (2004) showed that P. salmonis can be cultured in Sf21 insect cells with a yield approximately 60 to 100 times greater than that obtained in CHSE-214 cells and that the virulence for Atlantic salmon was unchanged. P. salmonis was cultured in four 175 cm 2 flasks containing confluent monolayers of Sf21 cells in 100 ml TC100 medium + 10% foetal calf serum (Invitrogen).…”
Section: Methodsmentioning
confidence: 97%
“…A significant difference was defined as a p-value of < 0.05. Birkbeck et al (2004) showed that intraperitoneal injection of Piscirickettsia salmonis SCO-95A is virulent for Atlantic salmon, with an LD 50 of < 2 × 10 3 TCID, but that only 1 of 20 cohabitant fish held in the same tank succumbed to SRS. Therefore, we exposed fish to 1 × 10 5 TCID ml -1 P. salmonis for 1 h in a bath challenge.…”
Section: Methodsmentioning
confidence: 99%
“…More recently, growth of R. felis in Drosophila melanogaster S2 cells was reported, with a cell infection rate of 100% after 19 days of incubation at 25°C (331). Other arthropod-borne bacteria, such as Diplorickettsia massiliensis (332), Wolbachia sp., and Bartonella bacilliformis (40), as well as other bacteria such as Piscirickettsia salmonis (333) and M. ulcerans (334) can also be cultivated more effectively by using this cell line.…”
Section: Cell Culturementioning
confidence: 99%